2020
DOI: 10.1371/journal.ppat.1008781
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression network analyses during infection with virulent and avirulent Trypanosoma cruzi strains unveil a role for fibroblasts in neutrophil recruitment and activation

Abstract: Chagas disease is caused by Trypanosoma cruzi , a protozoan parasite that has a heterogeneous population composed of a pool of strains with distinct characteristics, including variable levels of virulence. In previous work, transcriptome analyses of parasite genes after infection of human foreskin fibroblasts (HFF) with virulent (CL Brener) and non-virulent (CL-14) clones derived from the CL strain, revealed a reduced expression of genes encoding parasite surface proteins in CL-14 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…Besides, some researchers have suggested that both the parasite and host genetic variability could be the causes of differential clinical manifestations of Chagas disease ( Manoel-Caetano Fda and Silva, 2007 ). Also, transcriptomic analysis revealed differences between virulent and non-virulent strains ( Belew et al., 2017 ; Oliveira et al., 2020 ). Indeed, some T. cruzi strains highly differ in pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some researchers have suggested that both the parasite and host genetic variability could be the causes of differential clinical manifestations of Chagas disease ( Manoel-Caetano Fda and Silva, 2007 ). Also, transcriptomic analysis revealed differences between virulent and non-virulent strains ( Belew et al., 2017 ; Oliveira et al., 2020 ). Indeed, some T. cruzi strains highly differ in pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary studies reported that fibroblasts could secrete CX3CL1 to effectively prevent the adhesion and invasion of Candida [ 73 ]. Fibroblasts may also play indirect antifungal roles by recruiting and altering the functional status of immune cells through transforming growth factor-β1 (TGF-β1), granulocyte colony-stimulating factor (G-CSF), or CCL2 [ 74 , 75 ]. In addition, the crosstalk between fibroblasts and immune cells was reported in cancer [ 76 ].…”
Section: Interactions Between Candida and Hostmentioning
confidence: 99%
“…Previously RNA-Seq data [39][40][41] from human foreskin fibroblast cells infected with T. cruzi strain CL Brenner and Sylvio at 96 hours and 72 hours post-infection (hpi) were selected to generate a heat map. Four differentially expressed genes (GHR, IGF-1, IGF-1R, IGFBP3) RNA-seq data were extracted and plotted.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…The heat map generated, using previous RNA-Seq data [39][40][41] from differentially expressed genes, showed that during T. cruzi infection in human foreskin fibroblast cells GHR gene expression is downregulated (Figure 1a). Importantly, these data show that different T. cruzi strains (Sylvio, CL Brenner), at different times of infections (96 and 72 hpi), consistently downregulate GHR expression.…”
Section: Gh Modulates T Cruzi Infection Via Bioinformatic Analysis An...mentioning
confidence: 99%